Location-Aware Services and QR Codes for Libraries : (THE TECH SET® #13). - Murphy, Joe (Tech set ;, 2012)
The go-to resource for straightforward instruction on using Foursquare, Facebook Places, Gowalla, Bizzy, Google Wallet, augmented reality programs, and QR codes in your library!